SISTEM REALTIME KEAMANAN RUANG MENGGUNAKAN 2 WEBCAM BERBASIS HUMAN MOTION EXTRACTION - Yusron Rijal, Puput Widayanti (SPIRIT, 2014)
Security is very important that the rapid growth of technology and computer vision, many are trying to develop a computerized room security system that uses a computer and a webcam. This paper describes a realtime system security space using a webcam. Not only the webcams are used, but 2 is a webcam to webcam space with ample lighting and a webcam to a room without lighting. This meant that the system is capable of working in all ambient conditions, both light and dark. The method used in this study were human motion extraction method, namely extracting human movement affecting change the initial conditions of the room. used to recognize human movement proyection integral method. Projection integral values of objects similar to the integral value of the human being is considered as a projection of human movement.Keywords : space security systems, realtime, human motion extraction, integral proyection